Critical Study on Multimodality Perception in Higher Education Classroom - I Wayan Eka Dian Rahmanu; Lokman Altun; Ni Made Kariati (Politeknik Negeri Bali, 2020)
The image and audiovisual have been applied to create an innovative strategy in the English language instructional, whereas the combination of this instrument and digital technology which is known as “multimodality” has not been explored widely. This study gauges higher education students’ perception of multimodality. There were 87 Polytechnic and 41 University students involved in this research. Digital questionnaires were employed and the data collection was elaborated descriptively. The UTAUT model (unified theory of acceptance and use of technology) was applied to measure students’ argument on the multimodality use. The result indicated that there is a positive trend in the use of multimodality in the classroom. Learners have a desire to use the combination of image, audiovisual and digital technology. This study extends our understanding of what the learners need from digital technology development and a significant chance to develop on the multimodality which fit for the higher education level.